Apprenticeship governance and in-company training: where labour market and education meet : Cedefop community of apprenticeship experts: short papers - (:unkn) unknown (Publications Office of the European Union, 2021)
“There is an increasing shift of attention from expanding apprenticeships to improving their quality and effectiveness. This brings into focus how apprenticeship is governed for greater relevance and matching to labour market needs, and how the content of what is taught at the workplace is designed and delivered. This publication comprises papers drafted by members of Cedefop’s community of apprenticeship experts on these two topics. To complement the country-specific angle, Cedefop developed a comparative, cross-scheme and cross-country analysis and shared its reflections. The publication further documents Cedefop’s understanding that approaches to each topic may vary significantly between individual EU Member States. It also highlights that, even in cases of relative convergence, the fine details of how an apprenticeship scheme is designed and governed can make a significant difference to its relevance and quality, at least in stakeholders’ perceptions. Policy-making should take note of such details and their interconnections to understand how reforms can be better targeted and more effective and efficient.” (editor; BIBB-Doku)

Das europäische Zentrum für die Förderung der Berufsbildung (CEDEFOP) hat einen Bericht zu den Berufsbildungssystemen in Europa veröffentlicht. Der Bericht enthält Porträts der unterschiedlichen Berufsbildungssysteme innerhalb der EU. Dieser zeigt auf, was auf dem Weg zu einer höheren Qualität und Effektivität der Berufsbildung getan werden müsste. Beispielsweise fehle vielerorts eine echte und tiefgreifende Zusammenarbeit zwischen Bildung und Arbeitsmarkt. Der betriebliche Teil der Ausbildung müsse viel stärker auf einem strukturierten Ausbildungskonzept basieren. (BIBB-Doku)
Keywords: S System beruflicher Bildung; S 1.3 Berufliche Erstausbildung; S 4.3 Steuerung; I 2.2 Europa; 370; Berufsbildungssystem; Berufsausbildung; Betriebliche Berufsausbildung; Beziehung Bildungssystem Beschäftigungssystem; Arbeitsmarkt; Governance; Qualitätssicherung; Internationaler Vergleich; Europäische Union